The Association Between Maternal Age and Parity and the Incidence of Prolonged Labor: Maternal Age, Parity, and Prolonged Labor - Yudiarsi Eppang (CV. Paperhome Indonesia, 2026)
Background: Prolonged labor is one of the most common complications experienced by women during childbirth and remains a significant contributor to maternal and neonatal morbidity. Globally, prolonged labor is estimated to occur in approximately 17% of all deliveries, with nearly 70% of these cases requiring medical interventions such as cesarean section. In Indonesia, the incidence of prolonged labor is estimated at around 9% of all deliveries. Maternal factors such as age and parity are considered important determinants influencing labor outcomes. Therefore, identifying the relationship between these factors and prolonged labor is essential to improve maternal health services. This study aimed to determine the association between maternal age and parity and the incidence of prolonged labor at the Kassi-Kassi Community Health Center in 2024. Methods: This study employed an analytic approach using a cross-sectional design. The population consisted of mothers who delivered at the Kassi-Kassi Community Health Center in 2024. A total of 23 mothers were selected as the study sample using probability (random) sampling techniques. Data were analyzed using the chi-square test to examine the relationship between maternal age and parity with the incidence of prolonged labor. A significance level of p < 0.05 was applied. Results: The analysis showed a significant association between maternal age and the incidence of prolonged labor (p = 0.001; p < 0.05). Additionally, maternal parity was significantly associated with prolonged labor (p = 0.002; p < 0.05). These findings indicate that both maternal age and parity are important factors related to the occurrence of prolonged labor at the Kassi-Kassi Community Health Center. Conclusion: Maternal age and parity are significantly associated with the incidence of prolonged labor at the Kassi-Kassi Community Health Center in 2024. Strengthening maternal care services, particularly through closer monitoring of high-risk pregnant women, is recommended to reduce the occurrence of prolonged labor and improve maternal health outcomes.